Understanding of economic spillover mechanism by structural path analysis: A case study of interregional social accounting matrix focused on institutional sectors in Japan - Hidekazu Itoh (Journal of Economic Structures, 2016)
The aim of this research is to introduce a multiregional social accounting matrix (SAM) in Japan evaluating the regional and interregional spillover effects of economic impacts and to show the impact flows of economic linkages based on SAM. While research on national and regional SAM has become common, examples of interregional SAM are rare currently. This study points out that there is a substantial need to build a small regional and interregional SAM because of economic sensitivity. Our work evaluates the economic effects of national and regional government behavior, such as changes of the local tax system and decentralization of power, on the regional economy by structural path analysis. This research finds the differential impact flows of local government expenditures to regional incomes between a remote area and the rest of Japan (ROJ), or the leakages of remote area's money to ROJ via property income.
Keywords: C67; E16; O53; R15; 330; Input-output table; Interregional social accounting matrix; Structural path analysis; Japan